Mechanisms Regulating the Morphogenesis and Homeostasis of Epithelia - Brasal Prieto, Mariano; Huertas Fernández-Espartero, Cecilia; Martín Bermudo, María Dolores (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2025)
Motivation: Epithelia are robust tissues that support the structure of embryos and organs. These tissues have evolved diverse cellular architectures, which are acquired through a complex combination of cellular processes, including cell shape changes and cell migration. The control of these processes is fundamental for proper epithelia morphogenesis, and to maintain epithelial integrity in homeostasis and regeneration. Furthermore, disruption of these processes can lead to diseases, such as cancer. Thus, it’s imperative to understand the molecular and cellular mechanisms by which precise multicellular structures arise during development and become disrupted during disease. The follicular epithelium (FE) of the Drosophila melanogaster ovary provides us with a monolayered epithelium model, which, as part of its normal development, suffers a big event of morphogenesis, involving coordinated changes in cell shape and collective cell migration, which ultimately leads to elongation of the tissue and egg formation. This process is a potent model to perform functional and dynamic assays of epithelia morphogenesis in vivo. In the search for factors that could participate in this processes, we came across with capicua (cic). Cic is a transcriptional repressor involved in many types of cancer, and has been identified as mediator of EGFR in control of cell proliferation and cell differentiation. In this work, we focused on uncovering the role of cic in regulating cell shape changes and cell migration. Methods: We analysed morphogenetic events in Drosophila ovary in both wild-type and cic mutant conditions using different genetic approaches, such as Gal4/UAS and FRT/FLP systems. We are using in vivo confocal microscopy and biophisycal tools, such as laser ablation, to characterize the effects of modifying cic expression in cell and tissue shape. Results and Conclusions: We have shown that cic expression pattern changes during FE development. Functionally, down regulation of cic blocks changes in cell shape and cell migration leading to defects at a tissue level. Furthermore, cic loss of function induces alterations in the expression of two key regulators of cell shape changes, the actin cytoskeleton and the integrin adhesion proteins. These results lead us to propose a model in which cic might regulate the cell shape changes underlying epithelia morphogenesis acting as a repressor to modulate cytoskeletal and adhesion proteins levels.